Arterial Stiffness Is Associated With Basal Ganglia Enlarged Perivascular Spaces and Cerebral Small Vessel Disease Load - Riba-Llena, Iolanda; Jiménez-Balado, Joan; Castañé, Xavier; Girona, Anna; López-Rueda, Antonio; Mundet, Xavier; Jarca, Carmen I.; Álvarez-Sabin, José; Montaner, Joan; Delgado, Pilar (Stroke (1970), 2018)
BACKGROUND AND PURPOSE—We assessed whether the load of cerebral small vessel disease (cSVD) and its individual markers, including lacunes, white matter hyperintensities, microbleeds, and enlarged perivascular spaces (EPVS), are associated with arterial stiffness. METHODS—We evaluated cSVD markers in a cohort of 782 hypertensive individuals without history of stroke or dementia. The load of the disease was calculated using an ordinal scale ranging from 0 to 4 (1 point was given for each of the 4 markers examined). The arterial stiffness was tested by measuring the carotid–femoral pulse wave velocity with an oscillometric automatic device. RESULTS—The mean age of the participants (49.6% women) was 62.7±5.4 years, and the mean systolic/diastolic blood pressure was 142.9/77.3 mm Hg (55.5% of the participants had poor blood pressure control). We found 7.2% cases with lacunes, 6.4% with microbleeds, 6.7% with extensive white matter hyperintensities, 24.5% with extensive basal ganglia EPVS, and 40.1% with extensive EPVS in the centrum semiovale. Regarding the cSVD load, 19.7% of the participants scored 1, 6.5% scored 2, and 1.4% scored ≥3. The median carotid–femoral pulse wave velocity was 10.5 m/s (interquartile range, 9.2–11.9) and was associated with lacunes (odds ratio per carotid–femoral pulse wave velocity SD increase, 1.51; 95% confidence interval, 1.13–2.03), extensive basal ganglia EPVS (odds ratio, 1.39; 95% confidence interval, 1.16–1.67), and cSVD load (common odds ratio, 1.42; 95% confidence interval, 1.19–1.68). CONCLUSIONS—We found that, in a cohort of hypertensive individuals, the arterial stiffness is associated with the total load of the cSVD, especially with lacunes and basal ganglia EPVS.